Birtamimab plus standard of care in light-chain amyloidosis: the phase 3 randomized placebo-controlled VITAL trial - Gertz, Morie A.; Cohen, Adam D.; Comenzo, Raymond L.; Kastritis, Efstathios; Landau, Heather J.; Libby, Edward N.; Liedtke, Michaela; Sanchorawala, Vaishali; Schönland, Stefan; Wechalekar, Ashutosh; Zonder, Jeffrey A.; Palladini, Giovanni; et al. (Blood, 2023)
Amyloid light-chain (AL) amyloidosis is a rare, typically fatal disease characterized by the accumulation of misfolded immunoglobulin light chains (LCs). Birtamimab is an investigational humanized monoclonal antibody designed to neutralize toxic LC aggregates and deplete insoluble organ-deposited amyloid via macrophage-induced phagocytosis. VITAL was a phase 3 randomized, double-blind, placebo-controlled clinical trial assessing the efficacy and safety of birtamimab + standard of care (SOC) in 260 newly diagnosed, treatment-naive patients with AL amyloidosis. Patients received 24 mg/kg IV birtamimab + SOC or placebo + SOC every 28 days. The primary composite end point was the time to all-cause mortality (ACM) or centrally adjudicated cardiac hospitalization ≥91 days after the first study drug infusion. The trial was terminated early after an interim futility analysis; there was no significant difference in the primary composite end point (hazard ratio [HR], 0.826; 95% confidence interval [CI], 0.574-1.189; log-rank P = .303). A post hoc analysis of patients with Mayo stage IV AL amyloidosis, those at the highest risk of early mortality, showed significant improvement in the time to ACM with birtamimab at month 9 (HR, 0.413; 95% CI, 0.191-0.895; log-rank P = .021). At month 9, 74% of patients with Mayo stage IV AL amyloidosis treated with birtamimab and 49% of those given placebo survived. Overall, the rates of treatment-emergent adverse events (TEAEs) and serious TEAEs were generally similar between treatment arms. A confirmatory phase 3 randomized, double-blind, placebo-controlled clinical trial of birtamimab in patients with Mayo stage IV AL amyloidosis (AFFIRM-AL; NCT04973137) is currently enrolling. The VITAL trial was registered at www.clinicaltrials.gov as #NCT02312206.
Gesehen am 19.03.2024